2021
DOI: 10.1093/mnras/stab304
|View full text |Cite|
|
Sign up to set email alerts
|

Galactic potential constraints from clustering in action space of combined stellar stream data

Abstract: Stream stars removed by tides from their progenitor satellite galaxy or globular cluster act as a group of test particles on neighboring orbits, probing the gravitational field of the Milky Way. While constraints from individual streams have been shown to be susceptible to biases, combining several streams from orbits with various distances reduces these biases. We fit a common gravitational potential to multiple stellar streams simultaneously by maximizing the clustering of the stream stars in action space. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 93 publications
(175 reference statements)
3
47
0
Order By: Relevance
“…This work revealed abundant substructure in halos and discovered dozens of very low mass dwarf galaxies, providing dramatic confirmation of the widely accepted hierarchical galaxy formation paradigm (at least in part; Bell et al 2008). This sparked a vigorous theoretical exploration of how the galaxies' assemblies and mass distributions can be accurately measured from the remnants of disrupted satellites (Price-Whelan et al 2014;Sanderson et al 2015;Helmi et al 2018;Belokurov et al 2018;Lancaster et al 2019;Reino et al 2021). The Panchromatic Hubble Andromeda Treasury (PHAT; Dalcanton et al 2012) survey observations have revealed detailed insight about the formation and evolution of stars and disk galaxies (e.g., Rosenfield et al 2012;Williams et al 2012;Lewis et al 2015;Weisz et al 2015;Johnson et al 2016;Williams et al 2017) by resolving more than 100 million stars in the disk of M31 (Williams et al 2014).…”
Section: Recent Resolved Stellar Populations Studiesmentioning
confidence: 56%
“…This work revealed abundant substructure in halos and discovered dozens of very low mass dwarf galaxies, providing dramatic confirmation of the widely accepted hierarchical galaxy formation paradigm (at least in part; Bell et al 2008). This sparked a vigorous theoretical exploration of how the galaxies' assemblies and mass distributions can be accurately measured from the remnants of disrupted satellites (Price-Whelan et al 2014;Sanderson et al 2015;Helmi et al 2018;Belokurov et al 2018;Lancaster et al 2019;Reino et al 2021). The Panchromatic Hubble Andromeda Treasury (PHAT; Dalcanton et al 2012) survey observations have revealed detailed insight about the formation and evolution of stars and disk galaxies (e.g., Rosenfield et al 2012;Williams et al 2012;Lewis et al 2015;Weisz et al 2015;Johnson et al 2016;Williams et al 2017) by resolving more than 100 million stars in the disk of M31 (Williams et al 2014).…”
Section: Recent Resolved Stellar Populations Studiesmentioning
confidence: 56%
“…The resulting potential is therefore described by five parameters, namely the total mass M tot , the fraction of mass in the disc k, the scale length of the halo component a h , and the flattening parameters of the halo h and disc d . Here we set these parameter values to M tot = 4.0 • 10 11 M , k = 0.11, a h = 7.0 kpc, and h = 1.02, d = 75.0 (which are based on Batsleer & Dejonghe 1994;Famaey & Dejonghe 2003, see also Reino et al 2021, where two-component Stäckel potentials are fit to several streams around the Milky Way using Gaia DR2). The resulting potential matches the circular velocity curve of the Milky Way reasonably well, as shown in Fig.…”
Section: Choice Of the Potentialmentioning
confidence: 99%
“…Later, Sanders et al (2020) tested a true time-dependent BFE-based model and quantified the error in orbit reconstruction and showed high fidelity orbit reconstruction is attainable using BFE. Previous work focused on reconstructing and comparing the phase-space information of tidally disrupted star clusters of dwarf galaxies, but a lot of modern techniques use actions as proxies for preserving orbits (e.g., Sanderson et al 2015Sanderson et al , 2017O'Hare et al 2020O'Hare et al , 2020Reino et al 2020;Trick et al 2021). We are specifically interested in how well different models preserve the actions of stellar streams and the orbits of halo objects in realistic simulations of MW-like galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…These streams were first predicted from a galaxy merger simulation by Toomre & Toomre (1972) followed by the first observational discovery by Ibata et al (1994), Johnston et al (1995), and Newberg et al (2002) of a stream from the ongoing Sgr dSph merger, streams in globular clusters, and the Helmi streams (Grillmair et al 1995;Helmi & White 1999). These streams are excellent probes of the shape of the MW's radial mass profile (e.g., Koposov et al 2010;Bonaca et al 2014;Pearson et al 2015;Sanderson et al 2017;Reino et al 2020), its symmetry, (e.g., Law & Majewski 2010;Malhan & Ibata 2019) and, the orientation of its symmetry axes (Vera-Ciro & Helmi 2013;Vasiliev et al 2021;N. Panithanpaisal et al 2022, in preparation).…”
Section: Introductionmentioning
confidence: 99%